THE IRREGULARITY RELEASE OF RIGHTS TO WAQF LAND IN LAND ACQUISITION FOR PUBLIC INTEREST - Suyanto, Suyanto (International Journal of Law Reconstruction, 2022)
This study purpose was to investigate government regulation in land acquisition for public interest originating from waqf land, mechanism of release rights by nazhir to the state, and nazhir's position in the Waqf Law as waqf land manager. This study used normative legal research type, by using primary legal materials with philosophical approach, legislation and conceptual approach. The results were waqf land whose rights registration in the name of Nazhir cannâ€™t be transferred in any form of transfer rights, with exception of the transfer for public interest after obtaining written permission from the Minister with approval of the Indonesian waqf body which can be exchanged for objects whose benefits and exchange value are at least similarly. The provision of compensation in land acquisition after obtaining replacement land rights to waqf land are released by the waqf holder (nazhir) to the state. The mechanism doesnâ€™t go through the waiver of rights, because Nazhir is not the owner of the land, but through the mechanism of revocation of land rights, after Nazhir received compensation for land compensation, the state revoked the rights to the waqf land because the Law on the revocation of land rights in land acquisition is still in effect.Â